Salinity survival: molecular mechanisms and adaptive strategies in plants - Zhang, Huankai; Yu, Caiyu; Zhang, Qian; Qiu, Zihan; Zhang, Xiansheng; Hou, Yifeng; Zang, Jie (Frontiers in Plant Science, 2025)
Soil salinity is a significant environmental challenge that threatens plant growth and development, adversely affecting global food crop production. This underscores the critical need to elucidate the molecular mechanisms underlying plant salt tolerance, which has profound implications for agricultural advancement. Recent progress in plant salt tolerance has greatly improved our understanding of the molecular mechanisms of plant responses to salt stress and precision design breeding as an effective strategy for developing new salt-tolerant crop varieties. This review focuses on the model plant species Arabidopsis thaliana and important crops, namely, wheat (Triticum aestivum), maize (Zea mays), and rice (Oryza sativa). It summarizes current knowledge on plant salt tolerance, emphasizing key aspects such as the perception and response to salt stress, Na+ transport, Na+ compartmentalization and clearance, changes in reactive oxygen species induced by salt stress, and regulation of plant stem cell development under salt stress conditions. The review might provide new and valuable information for understanding the molecular mechanisms of plant response and adaptation to salt stress.